Syntheses, structures and catalytic coupling reactions of two tetrazolate-based coordination polymers. (27th July 2015) - Xu, Xin; Liu, Pei-Jiang; Yu, Ying-Hui; Hou, Guang-Feng; Gao, Jin-Sheng; Ma, Dong-Sheng
Graphical abstract: Two tetrazolate derivatives based coordination polymers are synthesized which both show three-dimensional hydrogen bonding supramolecular frameworks, and the property of them to catalyze the coupling reaction of α -amino acids and bromobenzene was also investigated. Abstract: Reactions of 5-(4-nitrophenyl)-1 H -tetrazole (H(4-nptz)) and 5-(4-nitrobenzyl)-1 H -tetrazole (H(4-nbtz)) with transition metals under solvothermal conditions yield two new coordination polymers, namely, [Cu I (4-nptz)(CH3 CN)] n (1 ) and [Zn(4-nbtz)2 ] n (2 ). Both of them were characterized by IR, thermogravimetric analysis, X-ray crystallography. Single crystal X-ray diffraction analysis reveals that1 is of three-dimensional (3D) sqc184 type supramolecular framework, while2 is of 3D sqc1 type supramolecular framework. In addition, solid state UV–Vis diffuse reflectance and photoluminescence properties of1 and2 are investigated. Furthermore, the catalytic properties for the coupling reaction of α -amino acids and bromobenzene were also investigated.